Drug utilization pattern of antimicrobial agents in postoperative patients of major surgery in the general surgical wards at a tertiary care teaching hospital - Gaikwad, Anushri P.; Barve, Rohidas M.; Jagtap, Rohini (International Journal of Research in Medical Sciences, 2025)
Background: Antimicrobial agents are prescribed very often inappropriately and have become one of the highly abused drugs. The widespread and indiscriminate use of antimicrobial agents results in emergence of antibiotic resistance. The World Health Organization (WHO) has prioritized the rational use of medications. To evaluate utilization pattern of Antimicrobial Agents in postoperative patients of major surgery. Methods: This was a non-interventional, observational, cross-sectional study, carried out in General Surgery Department at a tertiary care teaching hospital. Total 385 prescriptions of post-operative cases of major surgeries were analysed, to assess the pattern of antimicrobial agents prescribed, using hospital antimicrobial policy. Results: In this study number of male patients were 68% and female patients were 32%. Frequency of antimicrobial agents use in 385 patients was 1176 and among them, commonly prescribed antibiotics were metronidazole (92.98%) followed by ceftriaxone (49.35%) amikacin (46.75%) and piperacillin-Tazobactam (36.10%). In 49.35% of patients more than 3 antimicrobial agents were prescribed. Average number of antimicrobial agents per prescription were 3. Effectiveness of antimicrobial agents was confirmed by culture sensitivity report. Culture sensitivity test was done in 326 (84.67%). The percentage of antimicrobial agents used from the hospital antimicrobial policy was 74.82%. Conclusions: Due to fear of SSI and Hospital acquired infections, use of antibiotics for prolonged postoperative period adds economic burden and development of resistance. Thus, prescribers should be trained for proper implementation of antimicrobial policy and prevention of antimicrobial resistance.